Loranthus ferrugineus: a Mistletoe from Traditional Uses to Laboratory Bench - Omar Z. Ameer; Ibrahim M. Salman; Ko Jin Quek; Mohd. Z. Asmawi (Korean Pharmacopuncture Institute, 2015)
Objectives: Loranthus ferrugineus (L. ferrugineus) from Loranthaceae, a mistletoe, is a medicinal herb used for a variety of human ailments. Traditionally, decoctions of this parasitic shrub have been mainly used to treat high blood pressure (BP) and gastrointestinal complaints; usage which is supported by experimental based pharmacological investigations. Nonetheless, there is still limited data available evaluating this plant's traditions, and few studies have been scientifically translated toward evidence based phytomedicine. We therefore provide a concise review of the currently available L. ferrugineus literature and discuss potential directions for future areas of investigation. Methods: We surveyed available literature covering ethnopharmacological usage of L. ferrugineus and discussed relevant findings, including important future directions and shortcomings for the medicinal values of this parasitic shrub. Results: Evidence based pharmacological approaches significantly covered the medicinal application of L. ferrugineus for hypertension and gastrointestinal complaint management, with a particular focus on the active hydrophilic extract of this herb. Conclusion: Understanding the sites of action of this plant and its beneficial effects will provide justification for its use in old traditional treatments, and potentially lead to the development of therapies. Other medicinal applicative areas of this parasitic shrub, such as wound healing, gerontological effects, and antiviral and anticancer activities, are yet to be researched.